Utilisation of Forest Wealth - Sahib, Rao; Rangaswami, S. (Indian Forester, 1939)
The different classes of forest wealth, the forest areas in different countries, love of forests of the Japanese and the various advantages gained by all the Departments by forests are fully detailed. The prejudice against the Forest Department prevailing in the country, its cause and remedy, are explained. The importance of forest conservation in its relation to agriculture is fully explained. Various industries that can be developed by utilising forest resources are indicated. The possibilities of cultivation of medicinal plants and manufacture of various medicines explained as also the various uses of lac in different industries. Suggestions for exploring the mineral wealth of forests are given.